Study of Insulin Resistance and Glucose Transporter Protein 4 in Polycystic Ovarian Syndrome (Medical Forum Monthly, 2024)
Objective: To evaluate the relationship of Glucose transporter protein 4 and insulin resistance in patients of polycystic ovarian syndrome of various age groups. Study Design: Case control study Place and Duration of Study: This study was conducted at the Department of Gynaecology, Jinnah Hospital, Lahore from November 2018 to April 2019. Materials and Methods: This study included 58 polycystic ovarian syndrome women with age ranging between 1845 years, subdivided into three age groups. Rotterdam’s criteria were used to confirm the diagnosis of Polycystic ovarian syndrome. Results: The interpretation of the results revealed significantly high level of serum insulin and insulin resistance in patients suffering from Polycystic Ovarian Disease. Glucose transporter protein-4 levels in patient group were not found to be statistically significantly different in comparison to control. Conclusion: Insulin level in serum and insulin resistance is strongly associated with poly cystic ovarian syndrome. However, deranged glucose transporter protein- 4 is not always the case.